Utility and Access to 3-Dimensional Printing in the Context of Congenital Heart Disease: An International Physician Survey Study - Caroline F. Illmann, BSc; Martin Hosking, MD; Kevin C. Harris, MD, MHSc (CJC Open, 2020)
Background: Three-dimensional (3D) printing is a new technology capable of producing patient-specific 3D cardiac models. Methods: A cross-sectional survey of pediatric cardiologists was conducted. Members of the Canadian Pediatric Cardiology Association and Congenital Cardiac Interventional Study Consortium were invited to participate. A questionnaire was distributed using Research Electronic Data Capture between May and September 2019. Results were analyzed using descriptive statistics, Fisher exact test, and odds ratio. Results: A total of 71 pediatric cardiologists responded. Some 85% (60/71) agreed that patient-specific 3D printed cardiac models are a beneficial tool in treating children with congenital heart disease (CHD); 80% of those (48/60) believe 3D models facilitate communication with colleagues; 49% (35/71) of respondents had access to 3D printing technology; and 77% (27/35) of those were using models for clinical care. Access differed according to geographic location (P = 0.004). Of respondents, Americans were 5.5 times more likely (confidence interval, 1.6-19.2) than Canadians to have access to 3D printing technology. The primary reason for lack of access was financial barriers (50%, 18/36). In clinical practice, surgical planning is the primary use of models (96%, 26/27), followed by interventional catheterization planning (52%, 14/27). Double outlet right ventricle was the most commonly modelled lesion (70%, 19/27). Conclusion: 3D printing is a new technology that is beneficial in the care of children with CHD. Access to 3D printing varies by geographic location. In pediatric cardiology, 3D models are primarily used for procedural planning for CHD lesions with complex 3D spatial relationships. Résumé: Contexte: L’impression en trois dimensions (3D) est une nouvelle technologie permettant de produire des modèles cardiaques 3D sur mesure pour chaque patient. Méthodologie: Une enquête transversale a été menée auprès de cardiologues-pédiatres. Les membres de l’Association canadienne de cardiologie pédiatrique et du Congenital Cardiac Interventional Study Consortium ont été invités à y participer. À cette fin, un questionnaire a été diffusé au moyen de l’outil REDCap (Research Electronic Data Capture) de mai à septembre 2019. Les résultats ont été analysés au moyen de techniques de statistique descriptive, du test exact de Fisher et du rapport de cotes. Résultats: Au total, 71 cardiologues-pédiatres ont répondu au questionnaire. Environ 85 % (60/71) des répondants convenaient que les modèles cardiaques personnalisés à chaque patient et produits par impression 3D sont utiles pour traiter les enfants atteints d’une cardiopathie congénitale; de ce nombre, 80 % (48/60) estimaient que les modèles 3D facilitent la communication entre collègues; 49 % (35/71) avaient accès à la technologie d’impression 3D et, parmi eux, 77 % (27/35) se servaient de modèles pour prodiguer des soins cliniques. L’accès variait selon l’emplacement géographique (p = 0,004). Parmi les répondants, les médecins situés aux États-Unis étaient 5,5 fois plus susceptibles (intervalle de confiance : 1,6-19,2) que les médecins canadiens d’avoir accès à la technologie d’impression 3D. Les ressources financières constituaient le principal obstacle à l’accès à cette technologie (50 %, 18/36). Dans la pratique clinique, les modèles sont surtout utilisés pour planifier les interventions chirurgicales (96 %, 26/27) et le cathétérisme interventionnel (52 %, 14/27). Le ventricule droit à double issue était particulièrement modélisé (70 %, 19/27). Conclusion: L’impression 3D est une nouvelle technologie utile pour soigner les enfants présentant une cardiopathie congénitale. L’accès à cette technologie varie selon l’emplacement géographique. En cardiologie-pédiatrie, les modèles 3D sont surtout utilisés pour planifier les interventions relatives à des cardiopathies congénitales complexes sur le plan tridimensionnel.